Nanostructured graphene composite papers for highly flexible and foldable supercapacitors - Liu, Lili (2014)
Reduced graphene oxide (rGO) and polyaniline (PANI) assemble onto the surface of cellulose fibers (CFs) and into the pores of CF paper, to form hierarchical nanostructured PANI-rGO/CF composite paper. Based on these composite papers, flexible and foldable all-solid-state supercapacitors are achieved.